Strategi Peningkatan Potensi Sektor Unggulan Pertanian di Kabupaten Sidenreng Rappang - Andi Hardinah Arsyad (Departemen Ilmu Pemerintahan Fisip Unhas, 2024)
Rice is a strategic food commodity that plays a crucial role in supporting food security and regional economic growth. Sidenreng Rappang Regency, as one of the major rice-producing regions in South Sulawesi Province, faces various challenges in rice development, including the reduction of paddy field areas, limited irrigation infrastructure, climate change, and pest and disease outbreaks. This study aims to analyze the efforts undertaken by the Government of Sidenreng Rappang Regency in developing rice cultivation to increase rice production and support regional food security. The study employed a qualitative approach with a descriptive method. Data were collected through documentation studies, observations, and reviews of various sources related to food crop agricultural development. Data were analyzed descriptively to explain the strategies implemented in rice development. The results indicate that rice development has been carried out through the improvement of agricultural infrastructure, particularly irrigation networks, the provision of agricultural production facilities, farmer extension and assistance programs, and the management of production risks caused by climate change and plant pest disturbances. These efforts have contributed to maintaining agricultural productivity and supporting food availability for the community. However, several challenges remain and require further attention to ensure sustainable increases in rice production. Therefore, stronger policy support, enhanced farmer capacity, and optimized utilization of agricultural technology are needed to strengthen food security and promote sustainable agricultural development in Sidenreng Rappang Regency.